Treatment of osteomyelitis in New Zealand white rabbit using impregnated biomaterials with gentamicin: in vivo study outcome of bacterial study and micro-computed topography evaluation - Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli; Aziz, Aziah (Malaysian Orthopaedic Association, 2017)
INTRODUCTION: Treatment of osteomyelitis is still a major challenge in orthopaedic field. New Zealand White rabbit is acceptable experimental model described to develop effective local delivery of antibiotics osteomyelitis treatment as it can mimics the disease process in human. The objective of the study is to evaluate the outcome treatment of osteomyelitis in rabbit femur with impregnated Hydroxyappatite Gentamicin. Evaluation at stipulated durations using microCT Skyscan 1176 system.